Training a New Generation of Engineers for Digital Economy - A. N. Polyakov; I. D. Belonovskaya (Высшее образование в России)
The domestic engineering industry is going through the stage of system introduction of digital technologies. The purpose of article is to present an experience of the department in the formation of the competences of a future engineer demanded in digital mechanical engineering. The department implements training methods corresponding to basic elements of a national technological initiative matrix such as digital modeling, mechatronics, additive technologies, artificial intelligence in control systems. Students master digital modeling in the end-to-end course of 3D modeling when dealing with design tasks of increasing complexity requiring the synthesis of independent, creative and competitive activities of students. Mechatronic modules are studied and designed in the educational process as the engineering competences demanded by employers. Additive technologies are studied at a laboratory of fast prototyping; the method of training combines team creation of electronic models, receiving a prototype of a product, and presentation of a result at student’s professionally focused competitions. Systems of artificial intelligence define the content of research work in interaction “student – teacher”. The new types of career-guidance work such as popular scientific lectures, excursions and practical work on the hi-tech equipment are highlighted. The authors also dwell on the prospects of training a new generation of mechanics in the conditions of the coming digital economy: the introduction of high-tech teaching aids, the implementation of the experience of immersive environments, gamification of training, the development of competences providing comprehensive skills for servicing virtual production corporations and intelligent devices.